2020
DOI: 10.1108/ccij-01-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

Strategic management of public relations in Kuwait

Abstract: PurposeThe purpose of this paper is to help enrich the body of knowledge of public relations by exploring the status of the practice in Kuwait. Using the generic principles of public relations, a well-known theoretical framework in the field, we study the three major types of organizations: government agencies, nonprofits and corporations.Design/methodology/approachThe authors gathered data using a self-administered survey and qualitative interviews. In total, 250 questionnaires were distributed (both printed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The study's findings confirmed the significant positive association between the strategic approach to internal communication and employees' sense-making and sense-giving. This study provides new insights into organizational communication in a region of the world that has been largely understudied (Almutairi & Sriramesh, 2020). The findings contribute to the growing body of knowledge on the role of internal communication, especially from a strategic approach.…”
Section: Discussionmentioning
confidence: 72%
“…The study's findings confirmed the significant positive association between the strategic approach to internal communication and employees' sense-making and sense-giving. This study provides new insights into organizational communication in a region of the world that has been largely understudied (Almutairi & Sriramesh, 2020). The findings contribute to the growing body of knowledge on the role of internal communication, especially from a strategic approach.…”
Section: Discussionmentioning
confidence: 72%
“…Huang (2000) linked personal influence in Taiwan to Confucianism and societal harmony. More recently, personal influence has been identified as a central element in African public relations practices (Anani-Bossman, 2022;Anani-Bossman and Tandoh, 2023), in Kuwait CCIJ 29,7 (Al-Abdullah, 2021) and in both the Kingdom of Saudi Arabia and the United Arab Emirates (Abdelhay, 2014). These are regions of the world where power asymmetries are high and where interpersonal relationships are extremely important.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Have way better support and have staff available at all times because trouble shooting will arise and you should have super users which are people trained on this system available constantly at least the first year of implementation because when we did implement this and we would have issues it would take 30 minutes to one hour to get somebody to resolve a very simple issue and that does not help with the transition from paper to EHR.Alaslawi et al (2019) discussed the status and various trends of e‐health tools in Kuwait and pointed out that different sociopolitical, financial, infrastructural, organizational, technical, and individual barriers are hindering Kuwait from implementing EHRs. Almutairi's (2011) study was titled “A Strategic Roadmap for Achieving the Potential Benefits of Electronic Health Record System in the State of Kuwait,” and the author discussed the lag of implementation in Kuwait. The main factor causing the lag involved no clear plan for the implementation of EHRs in the country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adoption of EHR systems in Kuwait's healthcare has varied considerably, with only some government hospitals integrating their EHRs with other digital systems such as radiology and lab information systems, while other institutions only adopting fragments of digital solutions. This limited adoption is despite the establishment of central IT department to integrate electronic communication networks (Al‐Askari, 2003; Almutairi, 2011; Al‐Hazami, 2010; Alhuwail, 2019).…”
Section: Introductionmentioning
confidence: 99%